GOVERNMENT POLICY ON LAND CERTIFICATION FOR THE COMMUNITY THROUGH THE COMPLETE SYSTEMATIC LAND REGISTRATION (PTSL) PROGRAM IN CIKOKOL SUB-DISTRICT, TANGERANG DISTRICT, TANGERANG CITY - Gustiana , Rachmat; Agustin , Widya (Gapenas Publisher, 2025)
This research aims to explore and clarify the process of mass certification for state land under the Complete Systematic Land Registration (PTSL) program in Cikokol Urban Village, and whether it aligns with the core principles of land registration. A qualitative approach was used, with data gathered through interviews and field observations. Eleven informants were selected based on their insight and relevance to the issue. The Tangerang City Land Office designated Cikokol as a suitable location for the PTSL program because it met the criteria outlined in the Minister of Agrarian Affairs and Spatial Planning Regulation No. 6 of 2018 on Complete Systematic Land Registration. Ideally, the implementing team—particularly the Cikokol Urban Village officials—should carry out their roles in accordance with the established Standard Operating Procedures (SOPs). Doing so ensures the process runs smoothly and reduces potential misunderstandings, especially after the certificates are issued. This is crucial, as there have been complaints about unexpected costs related to BPHTB and SSP payments.